2018
DOI: 10.4018/ijtd.2018100103
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Weblog on Omani Learners' Writing Skills in the English Language

Abstract: The aim of this study is to investigate the impact of utilizing weblog on facilitating teaching writing at Buraimi University College (BUC) and to explore the extent to which a blog as a computer-mediated tool enhances learners' writing skills in English as a foreign language e(EFL), English as a second language (ESL). Vygotsky's model will be adopted in this study. Furthermore, a process approach is employed to involve students in writing. A mixed-method of qualitative and quantitative was embraced. Three ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…Additionally, in another study seeking to determine Kuwaiti undergraduate students' perceptions of Internet communication technologies in writing classes at a private HE institution in Kuwait, the results revealed that the students believed that the online tool was a valuable resource that provided them with the convenience and with the ability to learn on their own (Erguvan, 2015). Moreover, Alkhoudary (2018) aimed to examine how a blog as a computer-mediated tool develops learners' writing skills in English as a foreign language (EFL). The study's findings confirmed that integrating weblogs into teaching significantly impacts language learning at higher educational institutions.…”
Section: Online Learning In the Middle Eastmentioning
confidence: 99%
“…Additionally, in another study seeking to determine Kuwaiti undergraduate students' perceptions of Internet communication technologies in writing classes at a private HE institution in Kuwait, the results revealed that the students believed that the online tool was a valuable resource that provided them with the convenience and with the ability to learn on their own (Erguvan, 2015). Moreover, Alkhoudary (2018) aimed to examine how a blog as a computer-mediated tool develops learners' writing skills in English as a foreign language (EFL). The study's findings confirmed that integrating weblogs into teaching significantly impacts language learning at higher educational institutions.…”
Section: Online Learning In the Middle Eastmentioning
confidence: 99%
“…Dennis(2012)arguesthatmost activitiesintraditionalclassroomsdependonteacherlecturing,askingandansweringquestions.The currentconventionalmethodusesCDsorstereoplayerstoplaytheaudioforthewholegroup.In traditionalclassroom,teacherslecturematerialswhilestudentsreceivewithnoaction (Messier,2002). Classroomteachingaloneisnotenoughtocoverindividualrequirementsasindividualdifferencesare notconsideredandneglected.Additionally,Ahmadi(2017)maintainsthatoneofthemostimportant componentsforenhancingleaningoutputisthemethodsusedinclassrooms.Therefore,asynchronous learningisrequiredtoconstructautonomousenvironmentvialiveclassroomandcomputer-mediated buttheproblemisintheintrovertstudentswhoaredisregardedinESLclassrooms (Alkhoudary, 2018a).Itiscrucialtomingletwoapplicationstocreatemoreproductiveteachingmethod (Wangetal., 2009). Inst'anah(2017) (Alkhoudary,2018).…”
Section: Why Blended Learning Model?mentioning
confidence: 99%